(3cJGH GdbfGYI aj GdaYd GdeYJd EPG EJUd Hg hGh GdLeGYIs - (3jhSa GdUaJj,J (B1193 (3g` s ((3eMehO UObi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JfRg Yf GdCZQGV ai GdCaYGd hGdCMcGe hGdUdGI hGdSdGe Ydi SjOfG eMeO CeG HYO ajbhd GdYHO GdabjQ Edi Gddg JYGdi jhSa Hf GdTjN ESeGYjd bO cfJ CSeY cKjQkG ef GdfGS jdMf ai bhdg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bhdg QRbJ GdYde Ci QRbc Gddg GdYde GdfGaY GdehUd Edi Gddg JYGdi hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B274s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs